Magnetic Encoding Plasmonic Janus Microbead‐Based Suspension Array for High Sensitivity Multiplex Analysis. Issue 19 (15th May 2018) - Sheng, Tao; Xie, Zhuoying; Liu, Panmiao; Chen, Jialun; Chen, Shan; Ding, Hailong; Deng, Jingzhe; Yuan, Yi; Deng, Dawei
Abstract: In this study, a new kind of magnetic encoding Janus microbead‐based array with nanoplasmonic‐assisted fluorescence enhancement for highly sensitive multiplex immunoassay is developed. These plasmonic Janus microbeads are encoded by magnetic content and decoded by corresponding magnetic field intensity. With the plasmonic Janus microbeads, the fluorescence intensity has increased by a factor of 180 and the lower detection limit has improved by ≈1000‐fold—as low as 100 × 10 −15 m . The application of plasmonic Janus microbeads is also demonstrated in highly sensitive multiplex immunoassay. It is believed that the magnetic encoding plasmonic Janus microbeads will extend the application of nanoplasmonic‐assisted fluorescence enhancement of microbead‐based arrays in immunofluorescence analysis and have high potential in early diagnosis. Abstract : Magnetic encoding plasmonic Janus microbead‐based array is prepared for highly sensitive multiplex immunoanalysis. These plasmonic Janus microbeads are encoded by magnetic content and decoded by corresponding magnetic field intensity. Compared with the naked microbeads, the lower detection limit of the plasmonic microbeads has improved by ≈1000‐fold—as low as 100 × 10 −15 m .